Petani Jeruk di Bumi Tanadoang 1979-2017 - Muh. Nur Fajri Ramadhan; Ahmadin Ahmadin; Muh. Saleh Madjid (PATTINGALLOANG, 2017)
This paper attempt to provide an explanation of the description of orange farming in Batangmata Sapo. After having succes in rice self-sufficiency the government is giving more attention in the development of horticultural commodities. As well as South  Sulawesi region that increasing the economic growth and also develops a wide variety of business, one of them in the field of horticulture. Through the type of orange plant developed in the Luwu and Selayar areas. In 1979’s the coconut farmers was much higher more than of other cultivators. In the 1980’s people in this area are turning to cultivate oranges because that is considered more promising a better result than planting coconut. The Batangmata Sapo area that development the oranges agriculture for  the first time was in a village called Tamallua. Being farmed oranges is not always pan out, the disease and the season become a obstacle to farmers right now. This study is interesting to be studied because Batangmata Sapo is a center of orange production in Selayar Islands District because there are no one of researcher that looked at specifically. This research is a qualitative research with descriptive analysis approach, which consist of several stages namely: (1) Heuristic, by interviewing some orange  farmers such: Makmur, Taris, Muh. Daeng, Harundini. The archives collection at the Agriculture Department and Food Security of the Selayar Islands Regency, regarding orange production data in each year and also used a books that related to agriculture andorange crops such as Rahmat Rukmana's book entitled Tangerine farming (2) Criticism or the process of verifying the authenticity of historical sources. (3) Interpretation or interpretation of historical sources, and (4) Historiography, is the stage of historical writing.